Perbandingan Efektivitas Pembelajaran Clinical Skill Lab (CSL) dengan Menggunakan Video Ajar Keterampilan Klinik Neurologi terhadap Demonstrasi oleh Instruktur - Aryanty, Nindya; Puspasari, Anggelia; Purwakanthi, Anati (JAMBI MEDICAL JOURNAL "Jurnal Kedokteran dan Kesehatan", 2014)
ABSTRACT Background : Medical Faculty University of Jambi has been implemented  clinical skills lab (CSL) as one of learning methode. Limited time for encounter a learning topic which discuss just once in  learning session may effect student ability to perform clinical skill of learning topic. There are many research represent advantages of learning video as effective learning media to gained student memory  for a learning topic. The aim of this research was to compared effectiveness student clinical skill neurology examination ability using learning video with direct instructor teaching perform. Student ability to perform clinical skill assess using checklist procedure. Methode: This research was true experimental with posttest only control design. This research held at Medical Faculty University of Jambi in June until August 2014. Population of this research was all student in first years. Sample randomly selected and grouped as experiment (69 students) and control (68 students). Experiment group gave clinical skill neurology examination video, control group gave direct instructor teaching perform. Result: Evaluation based on checklist represent of experiment group had median value 78,13 (range 50,00) and control group had median value 74,25 (range 75,76). Mann U-Whitney test find the p- value for compared two group was 0,657 (p>0,05), there was no significant statistically between experiment and control group. Conclusion : In conclusion student who did not follow clinical skill learning session  can learned from video, video may consider as learning media to over come limitation human resources and time of lecture in medical faculty. Kata Kunci : Clinical Skill Lab, Learning video, Neurology clinical skill